PENGARUH MATH ANXIETY TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA BERDASARKAN GENDER - Kurnia Rahmi Yuberta; Widya Setiawati; Lely Kurnia (AGENDA: Jurnal Analisis Gender dan Agama, 2019)
Math anxiety often suffered by students in learning math. If it continues to appear, the students will not have a good ability on math concepts. Math concept actually is the basic ability in learning math. From a gender perspective, there is a difference in mathematics anxiety between male and female students. This research aims to seek out whether there is an influence of math anxiety on students’ comprehension of math concepts based on gender. The research method was the correlational research. The research subjects were the eighth grade students of MTsN 07 Tanah Datar. The research found there is a significant negative difference between math anxiety and the ability to comprehend math concepts based on gender at the eighth grade students of MTsN 07 Tanah Datar.